Photothermal enhancement of chemotherapy mediated by gold-silica nanoshell-loaded macrophages: in vitro squamous cell carcinoma study - Madsen, Steen J. (J Biomed Opt, 2016)
Moderate hyperthermia (MHT) has been shown to enhance the effects of chemotherapeutic agents in a wide variety of cancers. The purpose of this study was to investigate the combined effects of commonly used chemotherapeutic agents with MHT induced by near-infrared (NIR) activation of gold nanoshell (AuNS)-loaded macrophages (Ma). AuNS-loaded murine Ma combined with human FaDu squamous cells, in hybrid monolayers, were subjected to three cytotoxic drugs (doxorubicin, bleomycin, cisplatin) with or without NIR laser irradiation. For all three drugs, efficacy was increased by NIR activation of AuNS-loaded Ma. The results of this in vitro study provide proof-of-concept for the use of AuNS-loaded Ma for photothermal enhancement of the effects of chemotherapy on squamous cell carcinoma.